Penyusunan Asesmen Pembelajaran di SMPIT Darul Fikri Bawen - Joko Siswanto; Siti Patonah; Ummi Kaltsum; Ernawati Saptaningrum (Pelita: Jurnal Pengabdian kepada Masyarakat, 2022)
Assessment is an integral part of the learning process. SMPIT Darul Fikri Bawen as a service partner faces problems in the form of teachers' low ability in compiling questions based on basic competencies and the developed instruments still do not meet all aspects of the assessment. The purpose of this activity is to facilitate teachers in the SMPIT Darul Fikri Bawen environment in preparing evaluation instruments both offline and boldly. The method of activity used there are 3 stages, namely counseling and awareness, training, and assistance in preparing the instrument. The first stage begins with getting to know the types of evacuations, their benefits, and how to make them. In the second stage, participants are facilitated to make an assessment using google forms and google Classroom. In the last stage, participants are assisted from starting to analyze needs, develop assessments and use them in learning. The results obtained from this service activity are the results of the participant's knowledge about the types of evaluations and the ability to develop evaluation tools, both courage, and strength. The results of the evaluation showed that 90% of the participants were able to prepare evaluation tools well.